The Effects of Propolis Ethanol Extract on The Decreasing Number of The Mouseâs Spermatids Induced by Cigaretteâs Smoke - Sutikno, Mugi Tri; Muthmainah, .; Pesik, Riza Novierta (Nexus Biomedika, 2015)
Background:The propolis ethanol extract contains flavonoid, terpenoid, Caffeic Acid Phenethyl Ester (CAPE), vitamin A, vitamin C and vitamin E which are potential for being antioxidant to protect the spermatids from the danger of free radical. The aims of this research were to know the effects of propolis ethanol extract on the decreasing number of the mouseâs spermatids induced by cigaretteâs smoke and to know the effect of dosage raising level of the propolis ethanol extract towards the research subject. Methods:This research was a laboratory experiment using the posttest only controlled group design. The sampels were 25 Swiss Webster mice (age around 2-3 months and approximately 20 grams of weight). They were classified into 5 groups which consisted of 5 mice in each group. KK group was without any intervention. KI group was only induced by the cigaretteâs smoke. KP1, KP2Â  and KP3, all were induced by the cigaretteâs smoke and in a row, got 5.6 mg (dosage level I), 11.2 mg (dosage level II) and 16.8 mg (dosage level III) of propolis ethanol extract. These interventions were done for two weeks. The decreasing number of spermatids was counted through the inspection under microscope and counting of five chosen rounded-looks seminiferous tubules. The data were analyzed by One-Way ANOVA test and Post Hoc Multiple Comparisons test. Results:The result of One-way ANOVA p = 0.000 (p < Î±) showed differences between each research groups. The Post Hoc test of the spermatidâs number showed significant differences between KK-KI, KK-KP1, KK-KP2, KK-KP3, KI-KP1, KI-KP2, KP1-KP2, KP1-KP3, KP2 -KP3 groups but KI and KP3 wasnât. Conclusions:The propolis ethanolic extract can inhibit the decreasing number of the mouseâs spermatids which is induced by cigaretteâs smoke and the raising dosage from 5.6 mg to 11.2 mg is the succeeded dosage to inhibit the decreasing number of the spermatids. Keywords: propolis ethanol extract, spermatid, mouse, cigaretteâs smoke.